Evaluation Of Mud Logging And Wellsite Geology Data For Geothermal Feed Zone Identification In Well Dug-L6, Gea Field, South Sumatra - Saka Gea, Harmain; Kristanto , Dedy; Herianto, Herianto (Jurnal Offshore: Oil, Production Facilities and Renewable Energy, 2025)
Geothermal drilling requires precise identification of feed zones to optimize well productivity and minimize operational risks. This study evaluates the integration of mud logging and wellsite geological data for feed zone identification during the drilling of Well DUG-L6 in the Gea Field, South Sumatra. The research focuses on directional drilling within the 12¼” and 9⅞” sections, covering depths from 1300 to 2593 m measured depth (mMD). Real-time drilling parameters such as rate of penetration (ROP), weight on bit (WOB), standpipe pressure (SPP), and torque were analyzed alongside mud logging indicators and cuttings description. These datasets were integrated to identify anomalies including drilling breaks, circulation losses, temperature variations, and hydrothermal alteration that collectively serve as proxies for reservoir permeability. Results indicate three significant drilling breaks at 1388–1389.7 mMD, 1667–1669 mMD, and 2495.7–2497 mMD, each marked by abrupt increases in ROP, reductions in WOB, and thermal responses at surface level. Total loss circulation (TLC) occurred continuously from 1355 to 2593 mMD, confirming extensive fracture-related permeability in the deeper section. Cutting evaluation revealed lithologies dominated by dacitic lithic tuff and andesitic volcanic units, with hydrothermal alteration characterized by chlorite and illite mineral assemblages. These features are consistent with fluid–rock interaction and indicate the presence of active geothermal upflow pathways. Integration of drilling anomalies and lithological observations provided strong evidence of productive feed zones that align with structural targets defined in the subsurface model. This study demonstrates that real-time integration of drilling parameters and wellsite geological data provides a robust approach for early identification of geothermal feed zones. Two primary productive intervals 1300–1355 mMD and 2300–2593 mMD were delineated by the concurrence of significant drilling breaks, the onset and persistence of total loss circulation (from 1355 mMD to TD), BHCT anomalies exceeding 55 °C (peaks of 63.4 °C and 60.6 °C), and the presence of hydrothermal alteration minerals. These findings underscore the operational value of mud logging and wellsite geology as reliable, cost-effective tools for reservoir early characterization, enabling informed decision-making during drilling and supporting the sustainable development of geothermal resources in Indonesia.